Collision Characteristics During Autonomous Underwater Vehicle Recovery with a Petal Mechanical Gripper - Deyong Bian; Yuhong Liu; Manxing Yuan; Hongwei Zhang (Journal of Marine Science and Engineering)
Efficient underwater recovery systems are essential for battery recharging and data exchange of autonomous underwater vehicles (AUVs). This paper introduced a petal mechanical gripper (PMG) for AUV underwater recovery, and investigated the collision characteristics between the AUV and PMG during the recovery. A collision model was developed with Adams software 2018 to investigate the effect of the recovery mode and closure speed of a PMG driving claw on the recovery efficiency and AUV motion behaviors. A tank experiment was performed to validate the collision model. The simulation results indicated that the active recovery mode had a higher efficiency. Moreover, optimizing the PMG closure speed significantly reduced the recovery time and improved the AUV motion stability. This study provides valuable theoretical guidance for the effective recovery of underwater vehicles.